2023
DOI: 10.1111/twec.13406
|View full text |Cite
|
Sign up to set email alerts
|

Geopolitical competition, globalisation and WTO reform

Abstract: This paper discusses options to manage spillovers of unilateral trade policies motivated by national security and other non‐economic objectives on global trade and investment. Within the WTO framework, we argue a ‘specific trade concern’ mechanism is likely to be more effective than dispute settlement to address national security‐motivated trade intervention. More broadly, we propose creation of a platform for governments, supported by relevant international organisations, to enhance transparency and assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Beginning in 1995, this transparent dispute system operated relatively successfully in more than 500 cases. 1 This is part of a larger trend described by Hoekman et al (2023). These researchers stated that there has been a 're-emergence of trade as a national security issue' and that 'national security functions like a trump card in potentially allowing whoever can successfully establish a definition of an issue in terms of national security to dominate that issue' (p. 1168).…”
Section: The Demise Of the Appellate Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Beginning in 1995, this transparent dispute system operated relatively successfully in more than 500 cases. 1 This is part of a larger trend described by Hoekman et al (2023). These researchers stated that there has been a 're-emergence of trade as a national security issue' and that 'national security functions like a trump card in potentially allowing whoever can successfully establish a definition of an issue in terms of national security to dominate that issue' (p. 1168).…”
Section: The Demise Of the Appellate Bodymentioning
confidence: 99%
“…Pinchis-Paulsen (2020) summarised this, stating that 'the panel found that the Member invoking Article XXI does not have the sole authority to interpret the security exception provision-that Article XXI is not purely "self-judging"' (p. 113). Similarly, Hoekman et al (2023) stated: 'The panel adopted a two-tier standard of review: first scrutinising whether an emergency existed… and second limiting itself to a very deferential standard if an emergency was deemed to exist. Three subsequent WTO panels adopted this standard of review' (p. 1170).…”
mentioning
confidence: 99%
“…Global trade and investment scholarshipas published inter alia in the World Trade Review and encompassing political science, economics, and legal researchtends to focus on (1) why states opt for liberal or protectionist trade and investment policies (Hiscox, 2002;Rickard, 2015;Kim and Osgood, 2019); (2) why the design of Preferential Trade Agreements (PTAs) and International Investment Agreements (IIAs) varies over time and across country dyads (Allee and Peinhardt, 2014;Dür et al, 2014;Claussen, 2022); (3) whether such treaties and policies are legally compatible with the overarching principles of the World Trade Organization (WTO) and international economic law (Mavroidis, 2015;Pinchis-Paulsen, 2020;Hoekman et al, 2023); and (4) evaluate the complex economic, political, security, and environmental effects of these policies and treaties on societies (Bernauer and Nguyen, 2015;Roberts et al, 2019;Yildrim et al, 2020;Aggarwal and Reddie, 2021;Chaisse, 2023;François et al, 2023). Trade and investment scholarship has been highly productive over recent decades and has developed into a truly interdisciplinary and dynamic research enterprise.…”
Section: Introductionmentioning
confidence: 99%